2019
DOI: 10.1111/jcmm.14663
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the tyrosine kinase BMX mediates VEGFR2 expression

Abstract: Vascular endothelial growth factor receptors (VEGFRs) are major contributors to angiogenesis and lymphangiogenesis through the binding of VEGF ligands. We have previously shown that the bone marrow tyrosine kinase BMX is critical for inflammatory angiogenesis via its direct transactivation of VEGFR2. In the present study, we show that siRNA‐mediated silencing of BMX led to a significant decrease in the total levels of VEGFR2 mRNA and protein, without affecting their stability, in human endothelial cells (ECs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…The off target inhibition of BMX by BTK inhibitors could have therapeutic efficacy as well. For instance, BMX has increased expression in cardiac endothelium as a response to ischemia and is being looked at as a possible treatment for cardiovascular diseases (118)(119)(120)(121). It was also found that BMX regulates the TLR4 induced expression and TNF and IL-6, but IL-6 expression was independent of BTK inhibition of the p38 MAPK pathways (122).…”
Section: Btk Inhibitors Improving Selectivity and Changing Modes Of Actionmentioning
confidence: 99%
“…The off target inhibition of BMX by BTK inhibitors could have therapeutic efficacy as well. For instance, BMX has increased expression in cardiac endothelium as a response to ischemia and is being looked at as a possible treatment for cardiovascular diseases (118)(119)(120)(121). It was also found that BMX regulates the TLR4 induced expression and TNF and IL-6, but IL-6 expression was independent of BTK inhibition of the p38 MAPK pathways (122).…”
Section: Btk Inhibitors Improving Selectivity and Changing Modes Of Actionmentioning
confidence: 99%
“…The off target inhibition of BMX by BTK inhibitors could have therapeutic efficacy as well. For instance, BMX has increased expression in cardiac endothelium as a response to ischemia and is being looked at as a possible treatment for cardiovascular diseases (118)(119)(120)(121). It was also found that BMX regulates the TLR4 induced expression and TNF and IL-6, but IL-6 expression was independent of BTK inhibition of the p38 MAPK pathways (122).…”
Section: Btk Inhibitors Improving Selectivity and Changing Modes Of Actionmentioning
confidence: 99%